P387Revealing channels of interatrial communication during atrial fibrillation. (18th June 2020) - Pope, M; Kuklik, P; Briosa E Gala, A; Mahmoudi, MICHAEL; Paisey, J O H N; Betts, TIMOTHY
Abstract: Introduction: Interatrial propagation has been widely studied in anatomical specimens and electrophysiological studies during sinus rhythm or pacing. However, pathways of conduction during atrial fibrillation (AF) are poorly characterised in vivo. Purpose: We sought to develop a method of identifying the dominant channel of communication between atria during AF with a view to characterising the role of localised mechanisms in maintaining AF between both chambers. Methods: 10 patients undergoing simultaneous bi-atrial non-contact charge density mapping before and following pulmonary vein isolation (PVI) were analysed. Simultaneous 30s recordings during AF were obtained. Virtual electrograms from every vertex of the reconstructed left and right atrial (LA, RA) anatomies were exported and phase calculated using a method of sinusoidal recomposition and Hilbert transform. For each vertex, coherence between a sequence of activations between this point and every other point on the opposing chamber was calculated using mean phase coherence (MPC). The maximum of all MPC values was assigned to this local point to estimate the degree of coherence between activity at a given point and the entire opposing chamber. The regions with highest MPC value represent the channel of communication. Each activation of this zone is then evaluated and difference in local activation time between LA and RA determined (figure). Communication between atria is determined where a normal distribution of timing shift within this channel can be demonstrated (as opposed to a uniform histogram in the case of a lack of any correlation between electrograms). If seen to be preceding the opposite chamber for ≥60% of the recording then the chamber was deemed to be leading. Results: A total of 18 maps were obtained (pre-PVI only in 2). A clear channel of interatrial propagation could be seen in 17 maps (MPC value 0.48 ± 0.16) with communication within this channel demonstrated in 13 of these (MPC 0.52 ± 0.16). In the RA the most common site was in the posterior inter-caval zone (in 13) and on the posterior septum of the LA (in 14). The LA was leading in 4 maps and the RA in 2 with balanced propagation in 7. Conclusion: The method of average MPC identifies channels of inter-atrial communication during AF which appear to predominantly involve posterior interatrial connections. Further application of this technique to characterise interatrial propagation may help to define patient specific phenotypes of AF and guide targeted therapy.